Design And Cryptanalysis Of Encryption And Signature Schemes Without Certificates - Yap, Wun She (2007)
In this thesis, we focus on the design and cryptanalysis of signature and encryption schemes without certificates, particularly the identity-based and certificateless schemes. We review the existing schemes, and subsequently either successfully cryptanalyze the schemes or propose provable secure and efficient new schemes.